Asinominitas Dalam Pembacaan Kritis Atas Buku Al-Kitāb Wa Al-Qur`ān Qirā`AH Mu’āṣirah Karya M. Syaḥrūr - Andi Rahman (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Muhammad Syaḥrūr is one of the Islamic thinkers who introduces a new accounts related to the study of Qur’anic exegesis. By using historical and scientific approaches, he refuses the idea of sinonymity (tarāduf) in the Qur’an. For him, there is a substantial difference between “nabi” and “rasūl”, as well as other terms such as “al-kitāb, al-Qur’ān, al-ẓikr, and al-Furqān”. Based on his rejection to this idea, Syaḥrūr constructs his own theories concerning Qur’anic interpretation. There are several books that represent the anti-thesis to the Syaḥrūr’s ideas. This article tries to formulate its synthesis. With reference to the classic linguistic literatures, the author proves that the Qur’an contains the synonymities, and it apparently weakens the Syaḥrūr’s argumentation.[Muhammad Syaḥrūr merupakan salah satu pemikir kontemporer yang memperkenalkan wacana baru terkait penafsiran al-Quran. Dengan menggunakan metode historis-ilmiah (tārīkh-‘ilmi), ia menyatakan penolakan terhadap sinominitas (tarāduf) dalam al-Quran. Baginya, ada perbedaan substansial antara ”nabi” dan “rasul”, sebagaimana perbedaan ini ada pada term “al-kitāb, al-Qur’ān, al-ẓikr, and al-Furqān”. Berdasarkan penolakannya terhadap sinomintas, Shahrur membangun teori-teori penafsirannya. Ada beberapa buku yang memuat antitesa terhadap teori yang diperkenalkan oleh Syaḥrūr. Artikel ini mencoba merumuskan sintesanya. Dengan merujuk kepada literatur linguistik klasik, penulis membuktikan bahwa sinonimitas ada dalam al-Quran, dan wacana yang disampaikan oleh Syaḥrūr menjadi lemah argumentasinya.]